AR In Fashion Industry - Ranka, Dwaj; Mehta, Ranvir; Chopra, Pratham (2022 4th International Conference on Advances in Computing, Communication Control and Networking (ICAC3N), 2022)
Augmented reality is an on point or off point perspective of the real-world elements which are augmented over a computational program. It mostly increments the program information and improves the customer's perspective towards the real world. The main aim of this project is to create a virtual trial room program that helps the user simulate cloth movement in Augmented reality. The early applications were implemented over static images of the user and added static clothes over them. This is the common goal for each AR application. This application can require OpenCV and a webcam. Once there is a video captured, the application runs a series of codes to identify the background and the subject over which the cloth will be simulated. It is a well-versed platform that has been created for getting efficient computational functions. OpenCV holds multiple functions that are bonded with each other in identifying textures in different objects in a frame. After analyzing the color palettes, the image is turned into grayscale and thresholding is put on it to increase the intensity of the subject and decrease the ones of the background to a much darker intensity. Many works of the same threshold can be implemented on the picture on further requirement. Thresholding support is differentiating objects by compiling with their background functions and work on the pixels as required. On receiving the hierarchy, the objects are extracted and the detection on the required object starts kicking in with the application focusing onto it. Following the aforementioned task, the application can compute the required areas where the cloth is to be put and simulated on to the real world. The selection of the texture, color, patter, material is based on the users' preferences. The key difference between this technology and previous existing virtual halls is scarce hardware support on this virtual base.